(untitled) (Al-Academy, 2023)
The research section tagged (Aesthetics of Abstract Expressionism and its Representations in the Artistic Products of Students of the Department of Art Education) into four chapters and it included in..The first chapter: (the methodological framework) for the research, and the research problem is summarized through the question (what are the aesthetics of abstract expressionism and its representations in the artistic productions of the students of the Department of Art Education). In the products of students of the Department of Art Education).The aim of the research was (discovering the aesthetics of abstract expressionism and its representations in the artistic products of the students of the Department of Art Education). As well as the temporal and spatial boundaries that were confined to the University of Baghdad from the year (2021-2022) and then defining the terms (beauty, abstract expressionism).The second chapter included (theoretical framework) two sections, the first (aesthetics), while the second topic included (abstract expressionism) in addition to the indicators of the framework.In the third chapter (research procedures), the research community included a group of artistic works accomplished by the students of the Department of Art Education within the year (2021-2022), and then chose an intentional sample of (4), and it included the descriptive analytical approach, and the research evidence also included a sample analysis form.